ANALISIS YURIDIS TERHADAP KLAUSULA BAKU PERJANJIAN PEMBIAYAAN KONSUMEN PT. BIMA MULTI FINANCE PEKANBARU BERDASARKAN UNDANG-UNDANG NOMOR 8 TAHUN 2009 TENTANG PERLINDUNGAN KONSUMEN - Mila Puspita Sari; Maryati Bachtiar; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
The law is supposed to provide justice, because justice that the purpose of the law. Therefore already seyogianya when the laws governing credit institutions financing agreement also gives justice to the parties. In this connection, the contents of the clause-clause agreement between the credit institution and the customer Debitor financing cannot be based only upon the principle of freedom of contracts only. How Setting the raw clause in the agreement? How does the consumer agreement PT. Bima Multi Finance Soweto against law number 8 of 1999 challenge shield cover Consumers?This research will examine the subject matter of the problem in accordance with the scope and problem identification through juridical normative approach is a research that discusses the principles of law, systematic way of law, legal history and the synchronization level law, and comparative law. In this study the author examines the subject of legal arrangements regarding the synchronization level agreement against the raw clause with consumer protection.The provisions of clause making the ban on raw for the perpetrators of such effort in letter e of Article 18 paragraph (1), seem to need to be revised anyway. The prohibition for businessmen to make raw clause in the letter e should not only deal with the loss of usefulness of the goods or the utilization of services purchased by consumers, but also reduced the usefulness of the subject goods or services. So the full sound of the ban that is,